Actual problems of development of physical culture in modern society of Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
The problem of harmonization of body and soul as two inseparable entities connected with two hypostases of human existence was actual on all stages of history development in theoretical and practical aspects. Theoretical aspect is in that the mentioned problem is the ground basis for creating integral conception of a human being, which does not exist till now. Practical aspect is bound with that many peripeties of human history are connected with discord between soul and body.In present time actuality of the mentioned problem in global size is connected with anthropologic crisis – body, soul and spirit one. Actuality of soul and body harmonization is strengthened by the necessity of formation healthy way of life in the Republic of Kazakhstan, as development of the society directly depends on bodily and spiritual health of its members. In the article consider of the factors were revealed that inﬂ uence negatively on development of body culture in the Republic of Kazakhstan (social-economic, ecological etc), and three ways of body culture development were deﬁ ned: physical training, sport and healthy way of life.